Lonely in a crowd: loneliness in New Zealand retirement village residents. (15th May 2021) - Boyd, Michal; Calvert, Cheryl; Tatton, Annie; Wu, Zhenqiang; Bloomfield, Katherine; Broad, Joanna B.; Hikaka, Joanna; Higgins, Ann-Marie; Connolly, Martin J.
ABSTRACT: Objectives: The number of older people choosing to relocate to retirement villages (RVs) is increasing rapidly. This choice is often a way to decrease social isolation while still living independently. Loneliness is a significant health issue and contributes to overall frailty, yet RV resident loneliness is poorly understood. Our aim is to describe the prevalence of loneliness and associated factors in a New Zealand RV population. Design: A resident survey was used to collect demographics, social engagement, loneliness, and function, as well as a comprehensive geriatric assessment (international Resident Assessment Instrument [interRAI]) as part of the "Older People in Retirement Villages Study." Setting: RVs, Auckland, New Zealand. Participants: Participants included RV residents living in 33 RVs ( n = 578). Measurements: Two types of recruitment: randomly sampled cohort ( n = 217) and volunteer sample ( n = 361). Independently associated factors for loneliness were determined through multiple logistic regression with odds ratios (ORs). Results: Of the participants, 420 (72.7%) were female, 353 (61.1%) lived alone, with the mean age of 81.3 years. InterRAI assessment loneliness (yes/no question) was 25.8% ( n = 149), and the resident survey found that 37.4% ( n = 216) feel lonely sometimes/often/always. Factors independently associated with interRAI loneliness included being widowed (adjusted OR 8.27; 95% confidence interval [CI] 4.15–16.48), being divorced/separated/never married (OR 4.76; 95% CI 2.15–10.54), poor/fair quality of life (OR 3.37; 95% CI 1.43–7.94), moving to an RV to gain more social connections (OR 1.55; 95% CI 0.99–2.43), and depression risk (medium risk: OR 2.58, 95% CI 1.53–4.35; high risk: OR 4.20, 95% CI 1.47–11.95). Conclusion: A considerable proportion of older people living in RVs reported feelings of loneliness, particularly those who were without partners, at risk of depression and decreased quality of life and those who had moved into RVs to increase social connections. Early identification of factors for loneliness in RV residents could support interventions to improve quality of life and positively impact RV resident health and well-being.